Nutritional Improvement and Methane Gas Reduction of Poor Quality Roughages through Saccharomyces cerevisiae Fermentation in Sheep Feeding In-vitro (Journal of the Bangladesh Agricultural University, 2025)
This research was carried out the nutritive improvement of low quality roughages using yeast (S. cerevisiae) fermentation. Rice straw and Sugarcane bagasse were used as roughage substrate while the roughage mixture was made by rice straw and sugarcane bagasse at 1:3 ratio. Feeds were fermented with 0, 1, 3, 5, and 7% yeast for 5 days of incubation period. Results found that yeast fermentation increased the CP, TA, and NFE content of rice straw by 39.26, 7.49, and 13.53% respectively while reduced CF, EE, and ME by 24.45, 29.75, and 17.30% respectively, than non-fermented straw. Yeast fermentation increased 25.28, 38.72 and 31.25% TP, Ca and P content of the fermented straw. In in-vitro method result showed that The CH4 gas production decreased 8.78% in fermented straw. Maximum CP, TA, and NFE content of Sugarcane bagasse increased by 78.40, 48.60, and 14.77% respectively, and reducing CF, EE, and ME by 25.15, 62.5, and 13.86% than the control bagasse. Result showed that TP, Ca and P content of fermented bagasse increased by 38.70, 42.0 and 28.57% respectively and decline 39.97% CH4 gas production in-vitro trial. Fermented mixed roughage (Rice straw: Sugarcane bagasse; (1: 3) which was increased by 29.91% CP, 21.12% TA, and 16.91% NFE content and decreased by 26.71% CF, 34.61% EE, and 13.75% ME. Fermentation increased 24.56% TP content of roughage mixture. The CH4 gas production decreased 46.56% of fermented roughage mixture. The results showed that fermentation improved the TP, Ca and P content of the roughage mixture by 24.56, 35.53 and 34.0% respectively. After completing the research work the results found that nutritive value of poor quality roughages were increased significantly through   S. cerevisiae fermentation.J Bangladesh Agril Univ 23(2): 184-192, 2025